Genome-wide Identification, Characterization and Expression Profiling of SnRK Gene Family in Wheat: An in-silico Approach - Sharma, Manoj Kumar; Kumar, Sachin; Sharma, Manoj Kumar (Asian Journal of Biological and Life Sciences)
Sucrose non-fermenting 1 related protein kinases (SnRK) are well known for their crucial roles in responding to biotic and abiotic stresses through activating protein phosphorylation pathways in plants. So far, members of this important gene family have already been cloned and characterized and well-studied in different plant species. However, there is still a lack of comprehensive genomic information about SnRK gene family in wheat (Triticum aestivum L.) on genome-scale. It is vital to perform genome-wide identification and characterization of TaSnRK gene family in the wheat for an opportunity to improve the variety that have more and more abiotic resistance. In the present study, total of 5097 TaSnRK genes were identified in wheat genome using BLAST algorithm against the fully annotated reference genome available in Ensemble Plants 42.0 using AtSnRK2.1 protein from Arabidopsis thaliana as a query. Sequence analysis revealed that the coding sequence (CDS) length of inferred TaSnRK genes ranged from 210 to 7721bp, and corresponding protein length ranged from 69 to 2448aa. All the 5097 genes were studied for the stability of their proteins. Out of them 18 TaSnRK genes located on 11 different chromosomes with an uneven distribution were finally inferred to have a stable protein structure based on different parameters. The genes are classified into 9 subgroups on the basis of phylogenetic analysis. According to gene structure and motif analysis through MEME, the TaSnRKs showed obvious divergence among subgroups. Finally, the expression analysis revealed differential responses among the TaSnRK genes to osmotic stress. Overall, the present genomic and in silico analyses of TaSnRK genes offer a solid foundation for further investigation of functions of these identified genes, leading to improved variety of wheat against abiotic/osmotic stress.
Keywords: Abiotic Stress; Expression profiling; Functional annotation; Osmotic stress.; Sucrose non-fermentation-related protein kinase (SnRK) Wheat